2020
DOI: 10.3390/ijms21155560
|View full text |Cite
|
Sign up to set email alerts
|

PremPRI: Predicting the Effects of Missense Mutations on Protein–RNA Interactions

Abstract: Protein–RNA interactions are crucial for many cellular processes, such as protein synthesis and regulation of gene expression. Missense mutations that alter protein–RNA interaction may contribute to the pathogenesis of many diseases. Here, we introduce a new computational method PremPRI, which predicts the effects of single mutations occurring in RNA binding proteins on the protein–RNA interactions by calculating the binding affinity changes quantitatively. The multiple linear regression scoring function of Pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Protein stability is one of the most important factors that characterize protein function, activity, and regulation [1]. Missense mutations can lead to protein dysfunction by affecting their stabilities and interactions with other biological molecules [2][3][4][5][6][7][8][9]. Several studies have shown that the mutations are deleterious due to decreasing or enhancing the stability of the corresponding protein [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Protein stability is one of the most important factors that characterize protein function, activity, and regulation [1]. Missense mutations can lead to protein dysfunction by affecting their stabilities and interactions with other biological molecules [2][3][4][5][6][7][8][9]. Several studies have shown that the mutations are deleterious due to decreasing or enhancing the stability of the corresponding protein [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of various silent mutations can contribute to a change in protein structure and function, as well as their effect on protein folding, missense mutations can cause instability in protein function and the effect on interaction with other biological molecules (33). The occurrence of a number of mutations in more than one polymorphism may be due to the fact that these animals are of the same origin (34), but it is important to note that both the Italian and Brazilian polymorphisms share the same mutations with the polymorphisms obtained in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Although mCSM-NA generated a higher PCC value, its RMSE measure was approximately 3.5 times greater than our result. Moreover, we submitted MPR79 to the latest PremPRI webserver that was an extension of PremPDI for MPRs [43]. Although its training set included 31 overlapping mutations, PremPRI achieved worse PCC and RMSE metrics than our method.…”
Section: Independent Testing and Comparison With Existing Methodsmentioning
confidence: 99%